Health and responsibility: the relationship between parental illness and children's work in South Africa - Lane, T (2013)
South Africa faces a high disease burden and a limited public capacity to provide care to the ill. Research from the UK and sub-Saharan Africa suggests the burden often falls to children, who also take over domestic responsibilities necessary for household survival. To date, there is limited research exploring the relationship between parental illness and children’ responsibilities, or the moderating effect of socio-demographic variables. The thesis is comprised of three research phases. The first is a literature review to summarise existing research and identify substantial gaps, which included limited amounts of quantitative evidence on this topic and a lack of a tool to as-sess child responsibility that had both been adapted to the South African context and included caring responsibilities. The second research phase consists of an exploratory study of n = 349 children living with ill adults in urban and rural communities in the Western Cape province of South Africa to investigate their range of responsibility, which included caring for an ill parent, household chores, childcare, and income-generation. The resulting data were used to create the Child Responsibility Measure, which assesses the range and time burden of re-sponsibilities among South African children. The third research phase is a cross-sectional quantitative survey of n = 2,476 pairs of children and parents from urban and rural communities in KwaZulu-Natal province, South Africa. Resulting data on parental health, socio-demographics, and child responsibilities were analysed with multiple regres-sions to determine drivers of children’s responsibility. Among the findings were that parental illnesses increase the likelihood children provide care and have larger responsibility workloads, and girls are more likely to take on all types of responsibility excluding income-generating activities, which were more common in boys. Additionally, while urban children were more likely to provide personal care, rural children had greater responsibility workloads.